Small-scale irrigators’ intentions to adapt water use behaviour to climate variability in South Africa - Rachel M. Msila; Yonas T. Bahta; Henry Jordaan; Markus A. Monteiro (PLoS ONE, 2026)
This study aimed to determine the impacts of climate variability on smallholder maize producers’ water use behaviour and the factors that influence their decision-making in the Vhembe District Municipality, Limpopo Province, South Africa. This study utilized a survey from 366 smallholder maize irrigators, Theory of Planned Behaviour (TPB), and Structural Equation Modelling (SEM). The TPB posits that behavioural intentions can influence actual behaviour of individuals and groups, and it consists of three behavioural factors, namely attitude, subjective norms, and perceived behavioural control. Findings indicated that most of the farmers (96%) in the study area were dependent on farming as their primary occupation and livelihood. Most of the farmers were senior citizens with the mean age being between 51–60 and above 61 years of age, majority of the respondents (71%) had secondary education level and majority of the farmers (40%) had less than 10 years of farming experience and 35% had between 11–20 years of farming experience. In addition, the findings revealed that attitude, subjective norms, and perceived behavioural control significantly influence the small-scale farmers’ intentions to adapt to climate variability. The results suggest that as farmers’ attitudes become positive, their intentions to adapt enhance, and the perceptions of adaptation behaviours have a significant impact on individual farmers’ willingness to adapt. In addition, attitude and subjective norms have a substantial influence on the intentions of behavioural changes of farmers’ adaptation. However, perceived behavioural control does influence Intention but has a minor impact compared to attitudes and norms. Therefore, socio-psychological issues should be taken into consideration to improve smallholder farmers’ adoption of sustainable water use practices. This could raise smallholders’ livelihoods and agricultural productivity.